Reducing amount and frequency of meal as a major coping strategy for food insecurity - Adino Tesfahun Tsegaye; Amare Tariku; Abebaw Gebeyehu Worku; Solomon Mekonnen Abebe; Mezgebu Yitayal; Tadesse Awoke; Kassahun Alemu; Gashaw Andargie Biks (BMC, 2018)
Abstract Background Food insecurity is a global problem affecting many people worldwide, including approximately 220 million people in sub-Saharan Africa. Ethiopia is among the countries severely affected by hunger. However, evidence on how populations within Ethiopia cope with hunger and food insecurity is limited. This study aimed to identify household coping mechanisms in response to food insecurity at a Dabat Health and Demographic Surveillance System site. Methods This study used data from a re-census collected between October 2014 and December 2014.15,159 household members in thirteen kebeles of the Dabat Health and Demographic surveillance system were included. The outcome variables of the study were food insecurity and coping strategies. Household Food Insecurity Access Scale (HFIAS) was used to assess food insecurity. If food insecurity was found, families were asked about coping mechanisms used. Binary logistic regression analysis was applied to identify socio-demographic determinants of reducing amount and frequency of meal as a coping mechanism in response to food insecurity. Result Of the 15,159 households surveyed, 6671 (44.01%) reported the presence of a food insecurity in their household. Decreasing meal frequency and portions (3733 (55.96%)), borrowing money and food (2542 (38.11%)), and receiving food and money aid (1779 (26.67%)) were among the major coping strategies used by the households. Urban dwellers (AOR 2.07: 95% CI 1.74, 2.46), mid-altitude (weyina-dega) and high-land (dega) dwellers (AOR 2.46: 95% CI 2.08, 2.92 and AOR 1.22 95% CI 1.08, 1.38 respectively), and not married persons (AOR 1.60: 95% CI 1.07, 2.39) were more likely to consume less when faced with a food insecurity (using reducing amount and frequency of meal as a coping strategy). Conclusion Households in the study area experienced a very high rate of food insecurity. Decreasing meal frequency and portions was the primary coping mechanism used by the households. Due to the severe insecurity of food in their household, many people chose to reduce the amount and frequency of their meal in order to prolong the small amount of food in their house. This finding indicates a high risk for undernourishment which can exacerbate the burden of malnutrition and related diseases in the region.